2019
DOI: 10.1002/cam4.2639
|View full text |Cite
|
Sign up to set email alerts
|

MYST1/KAT8 contributes to tumor progression by activating EGFR signaling in glioblastoma cells

Abstract: With short survival time, glioblastoma (GBM) is the most malignant tumor in the central nervous system. Recently, epigenetic enzymes play essential roles in the regulation of tumorigenesis and cancer development of GBM. However, little is known about MYST1/KAT8/MOF, a histone acetylation enzyme, in GBM. The present study shows that MYST1 promotes GBM progression through activating epidermal growth factor receptor (EGFR) signaling. MYST1 expression was increased in GBM and was negatively correlated with prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Because lysine acetylation is mostly regulated by acetyltransferases and deacetylases, we used GPS-PAIL 2.0 software to make simple predictions for the seven acetyltransferases of the differentially acetylated proteins we quantified. Previous studies have shown that the down-regulation of acetyltransferase KAT3B induces apoptosis in renal carcinoma and the variations in the expression levels of MYSTI/MOF/KAT8 may affect the cell cycle and the EGFR signaling pathway ( Cocco et al, 2018 ; Dong et al, 2019 ). Additionally, our prediction results identified certain acetyltransferases with high scores, such as KAT8 which can act on Parp2 (K36/K51 site) and Casp3 (K25 site).…”
Section: Discussionmentioning
confidence: 99%
“…Because lysine acetylation is mostly regulated by acetyltransferases and deacetylases, we used GPS-PAIL 2.0 software to make simple predictions for the seven acetyltransferases of the differentially acetylated proteins we quantified. Previous studies have shown that the down-regulation of acetyltransferase KAT3B induces apoptosis in renal carcinoma and the variations in the expression levels of MYSTI/MOF/KAT8 may affect the cell cycle and the EGFR signaling pathway ( Cocco et al, 2018 ; Dong et al, 2019 ). Additionally, our prediction results identified certain acetyltransferases with high scores, such as KAT8 which can act on Parp2 (K36/K51 site) and Casp3 (K25 site).…”
Section: Discussionmentioning
confidence: 99%
“…2 e), the hub genes from the green yellow and yellow modules were the most connected, such as Supt16 , Psen2 , Gyg , Hgsnat , Vat1 , Mapkapk3 (green yellow), and the genes Prelid1 , Snx3 , Ost4 , Mvb12b , Kat8 , Pla2g2a , and Ttyh2 (yellow), followed by hubs from the blue, midnight blue, and light cyan modules. Among these hub genes, Supt16 is a component of the FACT (facilitates chromatin transcription) complex, and Kat8 codes for a lysine acetyltransferase that acetylates H4K16; both of which are altered in aggressive tumors [ 23 , 24 ]. In the midnight blue module, the hub Flt1 (fms-related tyrosine kinase 1) is a VEGF receptor that participates in the proliferation of melanoma cells [ 25 ], whereas Cdh5 (VE-cadherin) is highly expressed in metastatic melanoma [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…CSC phenotype [33] MOF (KAT8) Tumor promoter in GBM [34] AML, acute myeloid leukemia; AT-1/2, acetyl-CoA transporter 1/2; ATAT-1, alpha-tubulin Lysine acetylation can also be achieved in a non-enzymatic fashion (Figure 1), notably in the acetylation of calf thymus nuclear histone protein with acetyl-CoA, that is dependent on pH, period of incubation, ionic strength and ionic species [35]. Recent studies also suggested that, under basal conditions, "non-enzymatic lysine acetylation" is maintained at a very low stoichiometry in mitochondria [36,37].…”
Section: Nomenclature Mutation/aberration In Cancermentioning
confidence: 99%